Factories in the Fallows: The Political Economy of America's Rural Heartland, 1945-1980 - Orejel, Keith (2015)
This dissertation analyzes the economic and political transformation of America’s rural heartland after World War II. Examining the predominantly white, Protestant communities of southern Iowa and northern Arkansas, this dissertation shows how a prolonged economic crisis in the countryside gave rise to a grassroots pro-capitalist movement that came to dominate rural politics. Between 1920 and 1970, mechanization and scientific advancements pushed productivity in agriculture to remarkable levels. With capital investments replacing demand for labor, fewer workers were needed in farming. As job opportunities in agriculture disappeared, millions of people left rural areas. Country schools, churches, and businesses struggled to survive as populations dwindled. Many who stayed in rural communities suffered from widespread unemployment and poverty. Starting in the 1940s, small-town businessmen and state development experts proposed to solve this crisis by industrializing the countryside. Local boosters argued that newly acquired factories would stabilize rural areas by providing jobs for unemployed farmers and attracting new residents to small communities. Manufacturing payrolls were also expected to help local businesses by increasing consumer spending. In order to attract industrial plants, small-town business leaders modernized rural infrastructure—such as roads, sewers, and electrical systems—and improved civic institutions—including schools and hospitals. In the mid 1950s, these efforts began to pay off, as corporations started locating branch plants in rural areas. During the 1960s and 70s, rural America experienced an industrial boom, as many corporations left urban industrial centers in search of cheaper labor, lower taxes, and weaker unions. In the crucible of this campaign, small-town business leaders forged a unique political ideology that revolved around the imperatives of industrial development. To finance community and infrastructural upgrades, boosters argued for robust state and federal spending on vital improvements. Likewise, local elites favored economic planning over the free market, believing in rationally directed development. In order to lure capital investment, small-town business leaders manipulated the tax code to benefit corporate interests, while supporting legislation, such as anti-union right-to-work laws, that hampered organized labor. Local boosters also championed various governmental reforms meant to maximize efficiency and eliminate waste, concluding that this would produce enough revenue to fund necessary community improvements without raising taxes. In total, small-town business leaders believed that the central role of the American government was to spur capitalist development and private business growth. During the 1950s and 60s, small-town business leaders in southern Iowa and northern Arkansas campaigned to bring manufacturers to their communities, while also promoting their political vision within the countryside. As many depressed rural communities gained industrial plants during the 1960s, small-town business politics gained widespread popularity. In the late 1960s, the rural and small-town electorate united behind business backed “middle of the road” Republican politicians. Led by presidential candidate Richard Nixon, the GOP achieved a decisive political victory in 1968, winning electoral contests throughout America’s rural heartland. Since then, rural Americans have remained solidly Republican. However, GOP domination has been far from total. Starting in the mid 1970s, centrist Democrats competed for the rural electorate by embracing an economic agenda similar to their GOP rivals. After 1975, rural voters helped foster a bipartisan pro-business consensus, as both parties appealed to the countryside electorate by promising to spur economic growth with corporate friendly policies.